Clinical Experience Receiving ECMO for Acute Respiratory Distress Syndrome - AK, KORAY; KARAKURT, SAİT; OLGUN YILDIZELİ, ŞEHNAZ (AVES, 2017)
Acute respiratory distress syndrome (ARDS) is characterized by pulmonary edema caused by sudden increase in alveolocapillary membrane permeability, hypoxemia, and bilateral lung infiltration. Despite improvement in ICU treatment modalities, the mortality rate among ARDS patients is still considerably high. In the treatment of ARDS, in addition to the treatment of underlying cause, low-tidal volume, lung-protective mechanical ventilation is recommended. However, in patients who cannot attain target oxygen level or develop high plateau pressure despite low-tidal volume ventilation and who cannot tolerate high carbon dioxide and low pH levels, extracorporeal membrane oxygenation (ECMO) may be considered as a good treatment option. In this article, cases of ARDS patients treated with ECMO in our clinic during 2013-14 have been retrospectively documented and discussed in line with the literature.
Keywords: ARDS; ECMO; mechanical ventilation; hypoxia; EXTRACORPOREAL MEMBRANE-OXYGENATION; LIFE-SUPPORT EXPERIENCES; OUTCOMES; TURKEY; TRIAL; LUNG; ARDS